Anodic zno microsheet coating on zn with sub-surface microtrenched zn layer reduces risk of localized corrosion and improves bioactivity of pure zn - Dong, Hongzhou; Virtanen, Sannakaisa (Coatings, 2021)
Zinc-based alloys are emerging as an alternative to magnesium-and iron-based alloys for biodegradable implant applications, due to their appropriate corrosion performance and biocompatibility. However, localized corrosion occurring on the zinc surface, which is generally associated with restricted mass transport at specific surface sites, such as in confined crevices, declines mechanical strength and can lead to the failure of implant materials. In order to improve corrosion behavior and bioactivity, we explore the effect of a ZnO microsheet coating fabricated on pure Zn via anodic oxidization. Samples were characterized with Scanning Electron Microscope (SEM) (including Energy Dispersive Spectroscopy (EDS), X-ray Photoelectron spectroscopy (XPS), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD)). The microstructured surface consists of parallel Zn trenches on the bottom and ZnO/Zn3 O(SO4 )2 sheets on the top. This layer shows favorable Ca-phosphate precipitation as well as bovine serum albumin (BSA) adsorption properties. Electrochemical experiments indicate an increased corrosion resistance of surface-modified Zn by the presence of BSA in simulated body fluid. Most noteworthily, localized corrosion that has been previously observed for pure Zn in BSA-containing electrolytes does not occur on the Zn/ZnO-coated surface.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Albumin; Biodegradable metals; Corrosion behavior; Zn; ZnO

Corrosion behavior of biodegradable metals in two different simulated physiological solutions: Comparison of Mg, Zn and Fe - Dong, Hongzhou; Lin, Fei; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Corrosion Science, 2021)
Bio-absorbable metals have been proposed to overcome the limitations of permanent implant materials, particularly the risk of chronic inflammation and secondary surgery for removal after healing. The most researched bio-absorbable metal is magnesium, followed by iron and zinc, but there is little work comparing the different metals under the same experimental conditions. Herein, degradation performance of Mg/Zn/Fe was investigated via immersion test (28 days) and electrochemical tests under two buffer systems, simulated body fluid solution (SBF) and Dulbecco's Modified Eagle's cell culture medium (DMEM). Corrosion rate was initially slower in DMEM for all metals, Mg showed the fastest corrosion rate in both SBF and DMEM. The influence of the electrolyte on the corrosion behaviour was strongest for Mg. Importantly, the ranking of the corrosion rate of the three metals changes with immersion time. Noteworthy is a strong increase of corrosion resistance of Mg with time during the first 24 h of immersion. Corrosion morphology and corrosion products were characterized with SEM, EDS, FTIR, XPS and XRD. In general, the corrosion product layers are much more uniform in DMEM, besides, the insoluble corrosion product/precipitation consisted of metallic oxides/hydroxides, phosphates and carbonates. Slower corrosion rate in DMEM solution can therefore be due to formation of a more protective precipitate layer, adsorbed amino acids, and absence of Tris-HCl that accelerates corrosion in SBF.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Bioactivity; Biodegradable metals; Corrosion; Iron; Magnesium; Zinc

Fabrication of ZnO nanotube layer on Zn and evaluation of corrosion behavior and bioactivity in view of biodegradable applications - Dong, Hongzhou; Zhou, Juncen; Virtanen, Sannakaisa (Applied Surface Science, 2019)
Biodegradable materials are of great interest for the development of temporary implants. While most works have focused on Mg-based materials, recently, zinc and zinc based alloys are attracting increasing attention in this field. In this work, large scale area of flower structure zinc oxide nanotube (ZnO NT) layers were manufactured on the surface of pure zinc via anodic oxidation. Surface morphology and composition were characterized with SEM, XRD and XPS. The length of ZnO NTs was approximately 18 μm. Electrochemical tests in SBF solution showed that ZnO NT layers enhanced the electrochemical activity of pure zinc, from the perspective of degradation rate, the Zn/ZnO NT composite is more suitable for bone fixation compared with pure zinc. Immersion tests demonstrate that more Ca/P deposition occurs on the surface of ZnO NT samples, indicating a better biocompatibility compared with pure zinc. In addition, ZnO NTs have a large number of potential applications, such as use for drug release, or based on their catalytic and semiconductive properties.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Anodization; Bioactivity; Corrosion; Zn biodegradable materials; ZnO nanotubes

Influence of bovine serum albumin on biodegradation behavior of pure Zn - Dong, Hongzhou; Virtanen, Sannakaisa (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2021)
Zinc is emerging as a promising biodegradable metal for temporary implant applications. In this work, we investigate the influence of bovine serum albumin (BSA)—the most abundant blood protein in simulated body fluid (SBF) on degradation of pure Zn via electrochemical measurements and long-term immersion. Electrochemical experiments indicate a decrease of the corrosion rate of bare Zn with increasing BSA concentration in solution for short-term exposures. Samples were characterized with scanning electron microscope (SEM) (including energy dispersive spectroscopy [EDS], X-ray photoelectron spectroscopy [XPS], Fourier transform infrared spectroscopy [FTIR], and time-of-flight secondary ion mass spectrometry [TOF-SIMS]) after immersion up to 21 days. Presence of BSA in the electrolyte, decrease the amount of Ca-phosphate precipitation on Zn surface. However, a more compact surface layer formed in the presence of BSA in solution. Most noteworthy, in long-term exposures, BSA enhances localized corrosion of Zn—such detrimental localized attack was not observed in BSA-free solution. We suggest that a sealed space forming between the Zn substrate and a protein adsorption layer restricts mass transport, thus triggering localized corrosion of Zn.
CRIS-Team Scopus Importer:2021-07-16
Keywords: albumin; biodegradable metals; corrosion behavior; Zn